The differences of B2C and B2B workflow exception handling - Vojevodina, Dovilė; Kulvietis, Genadijus (Lietuvos matematikos rinkinys, 2005)
As business competition is getting stronger companies are seeking good relationships with their clients through the Internet technologies. The type of this relationship (B2Cor B2B) usually dependson the business strategy of this company. Using e-business technologies companies expect quick and qualitative contact with clients. Still, the quality of this solution depends on many aspects, but the main is application performance. The medium for these applications is Internet and it is not always reliable through all the engagement process. This paper is dedicated to the distinctions of B2C and B2B e-business application exception handling in a user friendly way.
Keywords: e-business; B2C; B2B; workflow; exceptions